2021
DOI: 10.3389/fcell.2021.720900
|View full text |Cite
|
Sign up to set email alerts
|

Lack of miR-379/miR-544 Cluster Resists High-Fat Diet-Induced Obesity and Prevents Hepatic Triglyceride Accumulation in Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) affects obesity-associated metabolic syndrome, which exhibits hepatic steatosis, insulin insensitivity and glucose intolerance. Emerging evidence suggests that microRNAs (miRNAs) are essential for the metabolic homeostasis of liver tissues. Many hepatic miRNAs located in the miR-379/miR-544 cluster were significantly increased in leptin-receptor-deficient type 2 mice (db/db), a mouse model of diabetes. However, the function of the miR-379/miR-544 cluster in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The deletion of the miR379 cluster attenuates hepatic steatosis and metabolic dysfunction of leptin-receptordeficient type 2 mice induced by a high-fat diet, and the insulin-like growth factor 1 receptor is directly targeted by miR379 [59]. In a study, ERS upregulated the megacluster miR379 along with lncMGC in the kidneys of diabetic mice and induced hypertrophy and fibrosis in mice.…”
Section: Discussionmentioning
confidence: 98%
“…The deletion of the miR379 cluster attenuates hepatic steatosis and metabolic dysfunction of leptin-receptordeficient type 2 mice induced by a high-fat diet, and the insulin-like growth factor 1 receptor is directly targeted by miR379 [59]. In a study, ERS upregulated the megacluster miR379 along with lncMGC in the kidneys of diabetic mice and induced hypertrophy and fibrosis in mice.…”
Section: Discussionmentioning
confidence: 98%
“…Also, hepatic miR-379-5p deficiency reduces serum very low-density lipoprotein-associated triglyceride (VLDL-TG) levels by promoting hepatic lipid reuptake and TG accumulation [60]. Recently, Cao and coworkers showed that the lack of miR-379/miR-544 cluster resists high-fat diet-induced obesity and prevents hepatic triglyceride accumulation in mice [61]. Dong et al lately reported that miR-379-5p inhibits STAT1 expression and regulates cholesterol metabolism through the STAT1/HMGCS1 axis in db/db mice, suggesting miR-379-5p might be applied to improve lipotoxicity and relieve diet induced-liver damage [62].…”
Section: Discussionmentioning
confidence: 99%
“…Different data in animals and humans show a relationship of certain miRNAs with hepatic metabolic homeostasis and leptin signaling. Many hepatic miRNAs located in the miR-379/miR-544 cluster were augmented in leptin-receptor-deficient type 2 mice and genetic mutation of this cluster in mice showed resistance to high-fat-diet-induced obesity with lower hypertriglyceridemia and steatosis [ 259 ]. Several compounds in modern diets are risk factors for the development of NAFLD and hepatocellular carcinoma, where various miRNAs are involved, with miR-650 being the most potent for the development of these diseases.…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%